2017
DOI: 10.1080/20445911.2017.1293065
|View full text |Cite
|
Sign up to set email alerts
|

Sequential learning in individuals with agrammatic aphasia: evidence from artificial grammar learning

Abstract: We examined sequential learning in individuals with agrammatic aphasia (n = 12) and healthy age-matched participants (n = 12) using an artificial grammar. Artificial grammar acquisition, 24-hour retention, and the potential benefits of additional training were examined by administering an artificial grammar judgment test (1) immediately following auditory exposure-based training, (2) one day after training, and (3) after a second training session on the second day. An untrained control group (n = 12 healthy ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…Such lasting priming effects in healthy speakers have been argued to reflect implicit learning rather than transient activation of primed structures (Bock et al, 2007; Bock & Griffin, 2000; Ferreira et al, 2008; Hartsuiker et al, 2008). Thus, in agrammatic speakers, these results are consistent with findings that implicit language learning ability may be spared (Schuchard & Thompson, 2014, in press) rather than impaired (Christiansen et al (2010); Zimmerer et al (2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Such lasting priming effects in healthy speakers have been argued to reflect implicit learning rather than transient activation of primed structures (Bock et al, 2007; Bock & Griffin, 2000; Ferreira et al, 2008; Hartsuiker et al, 2008). Thus, in agrammatic speakers, these results are consistent with findings that implicit language learning ability may be spared (Schuchard & Thompson, 2014, in press) rather than impaired (Christiansen et al (2010); Zimmerer et al (2014).…”
Section: Discussionsupporting
confidence: 88%
“…Some studies suggest that individuals with agrammatic aphasia show retained ability to learn novel linguistic sequences, including artificial grammars (Schuchard & Thompson, 2014, in press), whereas other studies report learning impairments (Christiansen, Louise Kelly, Shillcock, & Greenfield, 2010; Zimmerer, Cowell, & Varley, 2014). In Experiment 2 , we examined implicit language learning abilities by testing the lasting effects of structural priming (i.e., with two or four intervening sentences between prime and target sentences).…”
Section: Introductionmentioning
confidence: 99%
“…The results conflict with the idea that agrammatic aphasia is associated with damage to domain-general mechanisms that subserve both sequence learning and syntactic processing (Christiansen et al, 2010). Although previous studies have shown impairments in implicit sequence learning co-occurring with syntactic impairments after brain injury (Christiansen et al, 2010; Zimmerer et al, 2014), the present results suggest otherwise and support previous studies showing implicit sequence learning ability in people with agrammatic aphasia (Goschke et al, 2001; Schuchard & Thompson, 2014; Schuchard & Thompson, in preparation). Future studies should be designed to examine factors such as lesion site that may contribute to the variability in implicit learning abilities in this population, which will further the understanding of the neural mechanisms underlying learning and language.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, a study that used a visual artificial grammar showed implicit learning deficits associated with agrammatic aphasia (Christiansen, Kelly, Shillcock, & Greenfield, 2010). However, a separate visual artificial grammar study in which the results were analyzed at an individual level suggested that the extent and types of learning impairment are highly heterogeneous among individuals with aphasia (Zimmerer, Cowell, & Varley, 2014), and a recent study showed evidence of exposure-based artificial grammar learning in the verbal domain in people with agrammatic aphasia (Schuchard & Thompson, in preparation). If implicit learning processes are engaged in implicit treatment approaches, then the individual differences in implicit learning abilities that have been demonstrated in prior research may affect the outcomes of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative view of the role of LIFG in AGL comes from Schuchard and Thompson (2017). They used a PSG to generate strings of auditory syllables and found a similar, but relatively low, level of learning in agrammatic patients and controls after the first training session, but significantly superior learning in the controls after a second training session.…”
Section: Artificial Grammar Learningmentioning
confidence: 99%